Implementasi Interaksi Kolektif Dalam Pembelajaran Bahasa Arab di MTs Darul Huda Mayak Tonatan Ponorogo - Muhammad Ali Fatah; Muhammad Faza Fahiduzzaka; MUHAMMAD IBNU SHENA; Muhammad Rizki Ramadhan; Mz. Bhima Sakti; Nurul Malikah (Universitas 45 Surabaya, 2024)
Learning is a process of interaction carried out by students with educators and learning resources in a learning environment (Achjar, 2008). In a learning process, there are elements, namely educators, students, learning resources, environment, learning, and interactions which are interrelated. among these elements. (Gagne & Briggs, 1979) said that learning is a system that aims to assist the learning process, which contains a series of events that are designed, and arranged in such a way as to influence and support the internal learning process of students. In other words, learning is an activity that is deliberately planned and designed in such a way as to provide assistance to the learning process. In the learning process, there are 2 elements that can influence, namely internal and external elements. Internal elements are from learning itself, while external elements include things outside of learning that can influence one's own learning process.